Transient clusters in granular gases - Pöschel, Thorsten; Brilliantov, Nikolai V.; Schwager, Thomas (Journal of Physics: Condensed Matter, 2005)
The most striking phenomenon in the dynamics of granular gases is the formation of clusters and other structures. We investigate a gas of dissipatively colliding particles with a velocity dependent coefficient of restitution where cluster formation occurs as a transient phenomenon. Although for small impact velocity the particles collide elastically, surprisingly the temperature converges to zero. © 2005 IOP Publishing Ltd.